Experimental tests and finite element simulations of a new SMA-steel damper - Qiu, Canxing; Wang, Hongyang; Liu, Jiawang; Qi, Jian; Wang, Yanming (Smart materials and structures, 2020)
Owing to their outstanding recentering capability, shape memory alloy (SMA) dampers are emerging as promising passive dampers for seismic applications. However, compared to typical seismic dampers, the inherent energy dissipation capability of SMAs is often deemed barely satisfactory. To enhance the damping capacity of SMA dampers, this study suggests combining SMA elements with steel dampers based on bending steel plates. In this new SMA-steel damper, the steel dampers are mainly responsible for absorbing seismic energy, whereas the SMA bars primarily play the role of recovering inelastic deformation. Experimental tests were conducted at room temperature to verify the cyclic behavior of the proposed damper. The hysteretic parameters, such as strength, stiffness, equivalent damping ratio, and residual deformation, are of particular interest and quantified as a function of the loading amplitude. According to test results, the new damper is confirmed to possess desirable recentering capability and high damping. To further understand the damper, numerical simulations were carried out in the finite element (FE) analysis software ABAQUS. The numerical results validated the experimental data. Based on the calibrated FE model, the thickness of the bending steel plate of the steel damper and the diameter of the SMA bars were varied in the parametric analysis to examine its effect on the recentering tendency and damping mechanism.